Synthesis of Nano-Pomegranate Peel via Sol-Gel Method and Screen Characterization - Awatif I. Muhammed; Quraish A. Kazem; Rana A. Kamal; Ahmed J. Issa; Inas F. Abed; Salma Ali; Maan Ali; Safa Ali (Iraqi Journal of Industrial Research)
Nano peel solution was prepared using Sol-gel technology at a temperature of (80) Celsius. A number of tests were performed to describe the properties and structure of Nano material, including scanning probe microscopy (SPM), which showed the symmetric cumulative distribution of the solution Nanoparticles and the average grain size equal to 64.5 nm and the identical distribution of the Nanoparticles with a diameter of 37.75 nanometers, with a measurement area ranging between (1531.23-1558.19) nanometers. Nano-solution analyzed with a scanning electron microscope (SEM), Inspect type (S50), with a magnification power up to X2000, where dense flakes of Nano particles with a diameter of (50 ± 10) nanometers were observed. The antibacterial activity of Nano-solution by using gram- positive bacteria St. aurous and gram-negative E. coli show the inhibition diameter of (St. aurous) was 27 mm and 25 mm in (E. coli).